Infection Prevention and Management in Pediatric Short Bowel Syndrome - Merras-Salmio, Laura; Pakarinen, Mikko P. (Frontiers in Pediatrics, 2022)
Short bowel syndrome (SBS) is a rare disease, with potentially life-threatening consequences. In addition to intestinal failure associated liver disease, infections and other complications related to central venous catheters (CVC) cause a significant burden to SBS patients and may even necessitate an intestinal transplant eventually. The need for long term central venous access and the intestinal dysfunction associated with SBS drive the need for intestinal failure specific approach to preventing and treating infections in SBS patients. In bacterial infections the line can often be salvaged with proficient antibiotic therapy. Repeated catheter replacements predispose to recurrent infections and thrombotic complications which may limit long term survival of SBS patients. Protocol-based CVC access procedures and daily care including taurolidine and ethanol catheter locks have been shown to reduce infection rates substantially. Compromised intestinal function in SBS predisposes to small bowel bacterial overgrowth, mucosal injury, and increased permeability. These pathophysiological changes concentrate in a subset of patients with excessive bowel dilatation and frequent bowel derived infections. In such patients, reconstructive intestinal surgery may be indicated. Probiotics have not been effective in infection prevention in SBS and carry a significant risk of complications. While more studies focusing on the prevention of infections and their complications are needed, protocol-based approach and multidisciplinary teams in the care of SBS patients have been shown to reduce complications and improve outcomes.